PERAN STRATEGI POLITIK ISLAM TERHADAP PEREKONOMIAN DI INDONESIA - Hisyam Ahyani; Elah Nurhasanah (Prodi Hukum Ekonomi Syariah (Muamalah), 2020)
The development of Islamic economics is in a position to develop forward to very rapidly (Up to date), this starts with the emergence of several sharia financial institutions that have emerged along with efforts to accelerate economic growth in the community. Among the characteristics of the Islamic economic system is the emergence of demands to put more emphasis on the legal aspects and Islamic business ethics. So that the existing system in the Islamic economy there is an obligation to apply the principles of sharia and Islamic business ethics as well. Philosophically why the principles in Islamic economics must meet several criteria, including the principles of worship (al-tauhid), equality (al-musawat), freedom (al-hurriyat), justice (al-'adl), help- help (al-ta'awun) and tolerance (al-tasamuh). The strategic role of Islamic economics provides a very positive power for accelerating economic development in Indonesia through business partnerships with small and medium businesses. Empowerment of Islamic economics through a business partnership between Islamic financial institutions and small and medium businesses by developing real sector business activities in agriculture, such as agriculture, industry and trade as well as Islamic financial services and institutions, needs to be empowered and carried out to encourage the acceleration of national economic development and efforts to improve the economic welfare of the Indonesian people themselves.